Speaking Volumes: Musings on the Issues of the Day, Inspired by the Memory of Mary Joe Frug - Austin, Regina; Schneider, Elizabeth M. (Columbia Journal of Gender and Law, 2003)
Liz: The symposium began with a discussion about history-the history of feminism and of women’s law journals. Many of us who participated were part of this history, and Mary Joe Frug was as well. Since April 4, the day that the symposium was held, was the twelfth anniversary o fMary Joe’s tragic death, Regina and I were asked by the conveners of this symposium to bring Mary Joe into our conversations. Mary Joe was a feminist law professor at New England Law School. She had previously taught at Villanova Law School, and before that she had been a legal writing instructor here at Columbia Law School. She was murdered on April 4, 1991, in Cambridge, Massachusetts, where she lived. She was a dear friend of ours and Regina and I have both spoken and written on her work.